Executive Stock Option Contract Increases Firm Value and Performance: A Case Study on Starbucks Company (Global Journal of Management and Business Research, 2015)
A diversified stock option plan design plays a crucial role in the effectiveness of option contracts management and elimination of the free-rider problem. The aim of this study is to examine how a company can be used stock options in risk management and solving the agency problem rewarding employees and managers. The stock options plans offered by Starbucks engage all employees and executives into the ownership providing appropriate motivation and incentive and solving the agency problem. However, the study found that, this could also trigger more risk taking on the part of the top managers.
Keywords: contracts management and elimination of the free-rider problem